Influence of Sc on the microstructure, degradation behavior, biocompatibility in vitro and mechanical property of Mg-2Zn-0.2Zr alloy. (September 2022) - He, Yuqing; Wang, Richu; Yang, Liuzhong; Yang, Linyi; Liu, Hanchuan; Wang, Xinfa; Peng, Chaoqun; Feng, Yan
Graphical abstract: Highlights: Design degradable Mg-2Zn-0.2Zr- x Sc (ZK- x Sc, x  = 0, 0.2, 0.4, 0.6, 0.8, wt.%) alloys as potential implants. Investigate the effect of alloying element (Sc) on microstructure, degradation behavior and mechanical property of as-extruded ZK alloy. The addition of Sc in ZK alloy decreases the degradation rate and improves the ultimate tensile strength. Provide a better understanding on Sc as alloying elements for biomedical Mg alloys with superior mechanical property, slower degradation rate and good biocompatibility. Abstract: Microstructure, degradation behavior in vitro and mechanical property of as-extruded Mg-2Zn-0.2Zr- x Sc ( x  = 0, 0.2, 0.4, 0.6, 0.8, wt.%) alloys was investigated. Fine rod-like Mg(Zn, Sc, Zr) phase in as-extruded ZK-(0.4–0.8)Sc alloys inhibits recrystallized grains growth, resulting in grain refinement. The addition of Sc decreases the degradation rate in vitro and improves the mechanical property of ZK20 alloy. All tested alloys had no cytotoxicity effect on HUVEC and MC3T3-E1 cells. This work provides a better understanding on adding Sc as alloying element for biomedical Mg alloys with superior mechanical property, slower degradation rate and good biocompatibility.